Moderation of Foreign Ownership on the Relationship between Determinants and the Principle of Prudence in the Banking Sector - Vinola Herawaty; Florus Daeli; Indra Widiarto (Ilomata International Journal of Tax and Accounting, 2026)
This study aims to analyze the influence of financial distress, leverage, profitability, and firm size on the implementation of the prudence principle (accounting prudence) in the Indonesian banking sector, with foreign ownership as a moderating variable. Although prudence is crucial for banking stability, the current literature still shows inconsistent findings and limited evidence regarding the moderating role of global governance, which is a major gap in this study. The data analysis in this study was performed using SPSS software using a multiple linear regression approach. This model examines the influence of fundamental factors on the principle of prudence in the banking sector, using foreign ownership as a moderating variable to improve the accuracy of the empirical estimation results for a total of 129 data observations. Conversely, profitability had a significant negative effect, reflecting managers' tendency to be optimistic when financial performance improves to maintain market reputation. The unique contribution of this study lies in the finding that foreign ownership significantly attenuates the negative effect of profitability on prudence, demonstrating its role as an external monitoring mechanism in reducing managerial optimism bias. However, foreign ownership was not found to moderate the effects of financial distress or leverage. This study enriches the literature on agency theory in the context of emerging markets and offers practical implications for regulators to integrate foreign ownership structures as a supervisory instrument to enhance transparency and more robust banking risk management